Study on the ozonation degradation of methylene blue enhanced by microchannel and ultrasound. (24th January 2023) - Liu, Huiyang; Yu, Jianfeng; Liu, Xiangyu
Abstract: Azo dye-containing wastewater poses serious risks of environmental pollution because it is generally biologically toxic and resistant to conventional wastewater treatment methods. A novel degradation system integrating ozone, microchannel, and ultrasound was designed to effectively degrade azo dye-contaminated wastewater. The effects of discharge voltage of dielectric barrier discharge (DBD) reactor, liquid flow rate, microchannel width, ultrasonic power, initial pH, and reaction temperature on methylene blue (MB) decolorization were studied. A maximum MB decolorization efficiency of 92.7% was obtained in the ozone/microchannel/ultrasound (O3 /MC/US) system with 14 min of treatment. In addition, the 14-min decolorization efficiency and TOC removal efficiency obtained in O3 /MC/US system were increased by 12.6 and 6.5%, respectively, compared to those obtained in the pure O3 system. Based on the results of scavenging experiments, the combined effects of microchannel and ultrasound were proved to improve the contribution rate of hydroxyl radicals, thus improving the decolorization efficiency. The present work clearly illustrates that ozonation degradation can be effectively enhanced by microchannel and ultrasound, and also provides a feasible method for the treatment of organic wastewater. HIGHLIGHTS: Combined effects of microchannel and ultrasound on ozonation degradation were clearly observed. The 14-min decolorization efficiency of methylene blue reached 92.7%, which was increased by 12.6% due to the combination of microchannel and ultrasound. Ozonation degradation was enhanced by the combination effects of microchannel and ultrasound through the promotion of indirect ozonation process. Graphical Abstract